Humans First, Professionals Second: Impact of Psychological Distress on Counselling Self-efficacy and Empathy of Trainee Clinical Psychologists - Mariya Raza Noorani; Dr. Tahira Yousaf (Journal of Management Practices, Humanities and Social Sciences, 2022)
The current study aimed to find the relationship between the Psychological Distress (PD) of trainee clinical psychologists with their Counseling Self-Efficacy (CSE) and how this relationship may impact their empathy. It was hypothesized that (i) There will be a significant relationship between PD with CSE and empathy of trainee clinical psychologists, (ii) There will be a significant impact of the relationship between PD and CSE on the empathy of trainee clinical psychologists. A purposive convenient sampling technique was used to gather a sample of trainee clinical psychologists who have at least 1 month to 36 months of experience in client dealing and who are currently working in the field. A total sample of 103 (M = 25.92, SD = 2.73) was collected, including both males (5.8%) and females (94.2%). Participants of the study were provided an online form consisting of self-reported measures including the Kessler PD Scale (K10), Counselor Activity Self-Efficacy Scales (CASES) (Lent, Hill, & Hoffman, 2003), and Interpersonal Reactivity Index (IRI; Davis, 1980, 1996). Statistical analysis was done using Statistical Package for Social Sciences (SPSS) to interpret and further analyze scores. Pearson product-moment correlation showed a significantly weak positive correlation of PD with CSE (p-value < 0.05) and empathy (p-value < 0.01). Regression Analysis (R²=0.07) represented the variance caused by PD and CSE on empathy. This research is a base to appreciate the efforts of the clinical psychologists under training as well as a means to encourage them to accept their distress and seek help for it.